Maximizing the Utility of Transcriptomics Data in Inflammatory Skin Diseases - Wu, Jingni; Fang, Zhixiao; Liu, Teng; Hu, Wei; Wu, Yangjun; Li, Shengli (Frontiers in Immunology, 2021)
Inflammatory skin diseases are induced by disorders of the host defense system of skin, which is composed of a barrier, innate and acquired immunity, as well as cutaneous microbiome. These disorders are characterized by recurrent cutaneous lesions and intense itch, which seriously affect life quality of people across all ages and ethnicities. High-throughput transcriptomics data has proven unprecedented power to disclose the complex pathophysiology of inflammatory skin diseases. To elucidate molecular factors for typical inflammatory skin diseases (such as psoriasis and atopic dermatitis), transcriptomic profiling assays have been largely performed. Additionally, single-cell RNA sequencing (scRNA-seq) as well as spatial transcriptomic profiling have revealed multiple potential translational targets and offered guides to improve diagnosis and treatment strategies for inflammatory skin diseases. Here, we will summarize knowledge learned from transcriptomics data and discuss how to maximize the transcriptomics data to propel the development of diagnostic biomarkers and therapeutic targets in inflammatory skin diseases.